THE POPULATION OF MILA FACING THE EARTHQUAKE OF AUGUST 07, 2020 - Farida Sehili (International Journal of Innovative Technologies in Social Science, 2024)
The surge in urbanization within regions vulnerable to seismic activity poses a significant escalation in seismic risks. Effective mitigation strategies, reliant on improved architectural practices and behavioral adaptations, are imperative to curtail the toll of seismic events. Seismic vulnerability, intricately intertwined with seismic hazard, building conditions, and populace preparedness, underscores the need for comprehensive risk assessment. Although studies elucidating seismic risk knowledge and behaviors are scant in Algeria, they are more prevalent in Mediterranean regions. This paper delves into the examination of risk culture, discerning both direct and indirect causative factors behind the seismic disaster that befell Mila on August 7, 2020.Employing a research methodology that integrates the method Did You Feel It (DYFI USGS ) with a survey model used in Beirut, Lebanon.The findings offer notable insights for two principal reasons. Firstly, local perceptions of the seismic event's severity surpassed estimates by the US Geological Survey (USGS). Secondly, despite the relatively minor magnitude of seismic effects in the El Kherba neighborhood, the populace displayed inadequate preparedness for future earthquakes. Additionally, site-specific factors exerted substantial influence on crisis outcomes. In this context, the preparedness of Algerian society for seismic risks depends on understanding the phenomenon, recognizing associated hazards, and identifying available resources.Contribution: this study serves as a pivotal resource for fostering proactive local population preparedness and mitigating natural risks. Furthermore, it seeks to augment the efficacy of policies aimed at managing natural disaster risks in Algeria.